Análisis del mercado educativo de las instituciones de tercer nivel en la ciudad de Riobamba mediante teoría de juegos y la teoría del sistema de preferencias y competencia. - Luna Pérez, Cristian Sebastián (2023)
This investigative study aims to evaluate the feasibility of emulating the voucher concession system proposed by Milton Friedman in Ecuadorian third-level education. An algebraic demonstration of the reaction curve, coefficients, and the expression of utilities is presented; for this, the game theory is used, specifically, the dynamic oligopoly of Stackelberg, where: the National University of Chimborazo and the Polytechnic School of Chimborazo act as firms that compete for market share who, guided by the forces of supply and demand, would find their optimal levels of university places.